DEVELOPMENT OF VORTEX STRUCTURE OF FLAT TURBULENT JET LIMITED BY A FRONT - Isatayev, S.; Toleuov, G.; Isatayev, M.; Asembaeva, M. (Recent Contributions to Physics, 2021)
It is found that there can exist three types of a large-scale vortex. In case of sufficient compression of the nozzle, the jet of current is, as a rule, laminar at the output from nozzle. Owing to unstable current in vacant frontier layer discontinuous vortexes are formed, axis of which are parallel to the nozzle edge. These vortexes either set against end plate or circled on themselves, forming vortex ring.